PERAN KEARIFAN LOKAL DALAM UPAYA DERADIKALISASI FAHAM RADIKAL DI KALIMANTAN SELATAN - Syaugi Syaugi; Badrian Badrian; Faisal Mubarak (UIN Antasari Banjarmasin, 2020)
This article study discusses a portrait of religious insights among students and teachers in high schools in South Kalimantan. However, the conducted research is based on the background that the spread of radical ideology can be channeled through education, in which high school students are targeted by radical ideologies. This study intends to answer the question of how religious understanding and the role of local wisdom may encounter radicalism among Islamic education students and teachers. This article study finds that: Firstly, there are three categorizations can be mapped related to religious ideas emerging, namely: (1) Respondents whose militancy and radicalism narratives tend to dominate; (2) Some respondents also have moderation narration that dominates; and (3) some others have an equal narration of militancy and radicalism and moderation. Secondly: the locality of recitation through religious institutions of the majelis taklim with the content of Sufism-based recitation has a significant role for the students and teachers in responding to each religious issue based on moderation narration.Riset ini membahas potret faham keagamaan di dunia pendidikan dengan fokus pada siswa dan guru di Sekolah Menengah di Kalimantan Selatan. Hal ini dilatar belakangi bahwa penyebaran idiologi radikal dapat melalui jalur pendidikan, dimana siswa/siswi sekolah menengah atas dijadikan sasaran penanaman idiologi radikal. Penelitian ini untuk menjawab pertanyaan bagaimana pemahaman agama di kalangan siswa dan guru pendidikan Agama Islam? Bagaimana peran kearifan lokal dalam menangkal radikalisme di kalangan siswa dan guru pendidikan Agama Islam?. Penelitian ini menemukan bahwa: Pertama, ada tiga katagorisasi yang bisa dipetakan terkait narasi faham keagamaan yang muncul, yaitu: (1) Ada responden yang narasi militansi dan radikalisme cenderung mendominasi; (2) Ada responden yang narasi moderasinya mendominasi; (3) Ada yang antara militansi dan radikalisme di satu sisi dan moderasi di sisi lain berimbang (equal). Kedua: Lokalitas pengajian melalui lembaga keagamaan majlis taklim dengan konten pada pengajian berbasis tasawuf memiliki peran yang signifikan bagi siswa dan guru dalam merespons setiap isu keagamaan dengan basis narasi moderasi.